The Research Trend of Memorable Rural Tourism Experience: Systematic Literature Review and Bibliometric Analysis - Juliana Juliana; Sabrina O Sihombing; Ferdi Antonio (Budapest International Research and Critics University, 2022)
There are still many memorable experiences from traveling to the countryside yet to be revealed. This study aims to present emerging research trends regarding memorable experiences of rural tourism. A systematic literature review with bibliometric analysis was used to carry out this study. The results of the literature search and selection using the Scopus database determined 75 documents consisting of journal articles and conference papers published from 2018-2022. Performance analysis, science mapping, and networks were used to analyze data supported by PoP software and VOSviewer. The findings found that the trend of publications and citations of documents that examine memorable experiences when tourism in rural areas experienced a fluctuating development in the period 2018-2022. Furthermore, satisfaction is a feeling obtained from traveling in rural areas where tourist attractions in rural areas are also provide quality service by providing a place like a homestay where it is a memorable experience for traveling in rural areas. Therefore, rural tourism is one of the alternative activities that people can choose to minimize the level of boredom with the monotonous routine every day.